(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Background: The fifth generation (5G) technology is one of the modernist technologies in the wireless communications field. The design of antenna considers a vital role in 5G technology. In this paper, a proposed antenna is presented and investigated for 5G frequency band (28GHz). Materials and Methods: In this paper, a hexagon patch antenna, single and array patch antenna configuration at 28GHz are presented. The proposed antenna design is implemented on substrate (dielectric material ) of Rogers RT5880 with size of 8x8 mm2. Also, 1x2 antenna array sized of 10x16 mm2 and 1x4 antenna array sized of 13x32mm2 are constructed based on the proposed hexagon patch element. Results: Three configuration are implemented and simulated using the CST software. They are investigated in terms of the performance metrics represented by the Voltage Standing Wave Ratio (VSWR), gain, bandwidth, angular width, and total efficiency. The first configuration of a single hexagon antenna provides a gain of 7 dBi with excellent impedance matching (VSWR=1.259), an efficiency of 81%, an angular width of 165.6 degrees, and a bandwidth of 0.637 GHz. The second configuration of 1x2 hexagon antenna array achieves a gain of 8.9 dBi with excellent impedance matching (VSWR=1.9), an efficiency of 80%, an angular width of 48.2 degrees, and a bandwidth of 0.554 GHz. The third configuration of 1x4 hexagon antenna array demonstrates a gain of 12 dBi with excellent impedance matching (VSWR=1.45), an efficiency of 82%, an angular width of 18.8 degrees, and a bandwidth of 0.45 GHz. . Conclusion: The results highlight the impact of array geometry on gain, impedance matching, efficiency, angular coverage, and bandwidth. By elucidating these parameters, this research contributes to the advancement of millimeter-wave communication technologies, facilitating the design of high-performance antennas for various wireless communication applications in the 28 GHz frequency band.